The Impact of Implementing Total Quality Management (TQM) in Construction Companies: Focus on Employee Performance - Putry, Miranti; Restian, Ikmal (International Journal of Mechanical Computational and Manufacturing Research, 2024)
The importance of Total Quality Management (TQM) in construction companies is examined in this research. This research was conducted to determine the magnitude of the influence of TQM on improving employee performance. Theoretical frameworks, TQM practices, and employee performance improvement in construction companies are all examined. It was found that the better the implementation of TQM, it will encourage an increase in employee productive behavior, and through increasing employee productive behavior, overall company performance will also increase. Discipline in continuous quality improvement, encourages increased productive behavior of construction company employees.